2012
DOI: 10.1007/s00424-012-1087-x
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of inducible 70-kDa heat shock protein in mouse improves structural and functional recovery of skeletal muscles from atrophy

Abstract: Heat shock proteins play a key regulatory role in cellular defense. To investigate the role of the inducible 70-kDa heat shock protein (HSP70) in skeletal muscle atrophy and subsequent recovery, soleus (SOL) and extensor digitorum longus (EDL) muscles from overexpressing HSP70 transgenic mice were immobilized for 7 days and subsequently released from immobilization and evaluated after 7 days. Histological analysis showed that there was a decrease in cross-sectional area of type II myofiber from EDL and types I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 45 publications
3
26
0
1
Order By: Relevance
“…HSPs, especially HSP72 and HSP25, are inducible molecular chaperones that are upregulated when cells are exposed to stress (24). The upregulations of HSP72 and HSP25 prevent muscle atrophy, which is caused by disuse and/or immobilization (4,26,38). The transcription of HSPs is mediated by HSF1, which binds to heat shock elements located on HSP genes and induces their expressions (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HSPs, especially HSP72 and HSP25, are inducible molecular chaperones that are upregulated when cells are exposed to stress (24). The upregulations of HSP72 and HSP25 prevent muscle atrophy, which is caused by disuse and/or immobilization (4,26,38). The transcription of HSPs is mediated by HSF1, which binds to heat shock elements located on HSP genes and induces their expressions (24).…”
Section: Discussionmentioning
confidence: 99%
“…We previously showed that administration of the HSP inducer geranylgeranylacetone upregulated the expression of inducible 70-kDa HSP (HSP70 and so-called HSP72) and increased protein content in skeletal muscle cells (11). In addition, overexpression of HSP72 in skeletal muscle prevented immobilization-induced atrophy in rat (38) and improved the structural and functional recovery from atrophy of mouse muscle (26). It was also demonstrated that transfection of 27-kDa HSP (HSP27 and so-called HSP25) attenuated the disuse atrophy of rat muscle (4).…”
mentioning
confidence: 99%
“…Interestingly, there is a decline in expression of various HSPs in atrophied muscles of rats subjected to hindlimb unloading, which is predicted to be associated with impairment of muscle mass recovery (27,45,48). Furthermore, a recent study demonstrated that overexpression of HSP70 in mouse skeletal muscle immobilized for 7 days resulted in improved contractile performance during the recovery period relative to wild-type controls, indicating that HSP70 improved recovery of skeletal muscle following disuse atrophy (34). In C. alboguttata the upregulation of genes involved in refolding and stabilizing proteins in gastrocnemius muscle may be important regulatory mechanisms contributing to the preservation of muscle contractile performance upon emergence from estivation.…”
Section: Cell Death and Survivalmentioning
confidence: 99%
“…Second, upregulation of HSP70 was associated with the maintenance of muscle mass and function in the porcine ICU model when animals were only exposed to immobilization, MV, muscle relaxants, and sedation (1,6). It has also been shown that HSP70 directly regulates skeletal muscle atrophy via FOXO signaling (30) and that inducible HSP70 overexpression improves skeletal muscle structure and functional capacity (24).…”
Section: Discussionmentioning
confidence: 97%